Pengembangan Aplikasi Konseling Teman Sebaya SATRIA (Siswa Asuh Tangguh Rangkul Insan Sebaya) sebagai Pelatihan Peer Counseling berbasis Website - Julius, Andre; Wijana, Miki; Nurlatifah, Sari; Alfaiz, Alfaiz (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
This research aims to assessment and develop a new approach for developing a potential of students as peer for another. This research developing an application based on website, which consist of such workshop, psychological testing, and counseling. This development using ADDIE model, with curriculum merdeka belajar this application will needed for better quality in student’s education and learning, first phase in this research was Analysis which is about preliminary studies about need for SATRIA, and then Design this phase such arranging about design application and website also about content, Development this phase such developing a process website such domain and also content and menu in this website. Result of this research was the product SATRIA has been made and still on process in Implementation and Evaluating, becauses this research is Research and Development of a product for workshop and training for peer counseling and psychological test, so this research need developing for further.